TALENT MANAGEMENT IN WORK-LIFE - A LIGHTNING BOLT TO YOUR PROFESSIONAL DEVELOPMENT! - Parameswaran, Hima (PEOPLE: International Journal of Social Sciences, 2019)
Organizations in this 21rst century face numerous challenges as a result of increased demographics and diversity of the workforce. In this context, companies require an organized and strategic effort to use various human resource management practices, including acquiring employees, learning and development, performance management, and compensation to attract, retain, motivate, and develop highly skilled work-force.This research not only helps to explore the relationship between HRD in a Public and a Private organization, also it facilitates a framework to develop employee self-confidence and cheerfulness by a constructive work environment. Simultaneously, it is vital to depict the outcomes of two independent variables viz. Talent management and, Professional development towards its dependent variable, HRD. It highlights on the employee perception about working conditions of the two companies, which is a fundamental factor for the leadership skills, employee commitment, high performance work systems, and the necessity of socio-technical systems. Accordingly, the study is concentrated at Kochi, Kerala, India, in the shape of ‘Comparative Analysis of HRD in a Public and a Private’ (quantitative and qualitative analysis) with a focus on the Plant level workers and the Managerial staff (stratified proportional sampling) with a sample size of 481 and 475 from both companies. Furthermore, it has been statistically verified that two factors show a positive relationship with HRD. Along with this, it identifies the extent to which the HRD and its work-life factors are provided by the selected companies. The outcome of the survey has generated a relationship between dependent variable (HRD) and independent variables (work-life factors), different opinion in their HRD, their outlook about HRD and work-life factors with respect to demographic factors, personal satisfaction about their HRD, varying satisfaction level with respect to the demographic factors, and the influence of HRD variables in the selected companies.